Alterations of retinal thickness measured by optical coherence tomography correlate with neurophysiological measures in diabetic polyneuropathy. Issue 8 (30th December 2020) - Yamada, Yuichiro; Himeno, Tatsuhito; Tsuboi, Kotaro; Shibata, Yuka; Kawai, Miyuka; Asada‐Yamada, Yuriko; Hayashi, Yusuke; Asano‐Hayami, Emi; Hayami, Tomohide; Ishida, Yuichiro; Ejima, Yohei; Motegi, Mikio; et al.
Abstract: Aims/Introduction: Diabetic polyneuropathy (DPN) and diabetic retinopathy (DR) are traditionally regarded as microvascular complications. However, these complications may share similar neurodegenerative pathologies. Here we evaluate the correlations in the severity of DPN and changes in the thickness of neuroretinal layers to elucidate whether these complications exist at similar stages of progression. Materials and Methods: A total of 43 patients with type 2 diabetes underwent a nerve conduction study (NCS), a macular optical coherence tomography, and a carotid artery ultrasound scan. Diabetic polyneuropathy was classified according to Baba's classification using NCS. The retina was automatically segmented into four layers; ganglion cell complex (GCC), inner nuclear layer/outer plexiform layer (INL/OPL), outer nuclear layer/photoreceptor inner and outer segments, and retinal pigment epithelium (RPE). The thickness of each retinal layer was separately analyzed for the fovea and the parafovea. Results: Fourteen patients were classified as having moderate to severe diabetic polyneuropathy. The thicknesses of the foveal and parafoveal INL/OPL increased in patients with diabetic polyneuropathy compared with patients without. The thickness of the parafoveal retinal pigment epithelium decreased in patients with diabetic polyneuropathy. The thinning of parafoveal ganglion cell complex and foveal and parafoveal retinal pigment epithelium were positively correlated with deterioration of nerve functions in the nerve conduction study, but the thickening of INL/OPL was positively correlated with the nerve function deterioration. The thinning of parafoveal ganglion cell complex and foveal retinal pigment epithelium were positively correlated with the thickening of the carotid intima‐media. Conclusions: Depending on the progression of diabetic polyneuropathy, the ganglion cell complex and retinal pigment epithelium became thinner and the INL/OPL became thicker. These retinal changes might be noteworthy for pathological investigations and for the assessment of diabetic polyneuropathy and diabetic retinopathy. Abstract : (1) The thickness of the foveal and parafoveal inner nuclear layer/outer plexiform layer increased in patients with clinical diabetic polyneuropathy compared with patients without clinical diabetic polyneuropathy. (2) A decrease in the thickness of the parafoveal ganglion cell complex correlated with deterioration of nerve functions in the nerve conduction study. (3) A decrease in the thickness of the parafoveal ganglion cell complex was positively correlated with an increase in the parameters of atherosclerosis and cardiovascular risk factors.